1982
DOI: 10.3109/08820138209050746
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response to Basic Protein and T Suppressor Cells in Multiple Sclerosis

Abstract: Peripheral blood lymphocytes from patients with multiple sclerosis (MS) and two control groups, patients with neurologic diseases other than MS and healthy individuals, were examined for their cellular response to basic protein (BP), suppressor cell activity elicited by concanavalin A (ConA) and enumeration of T gamma cells. Lymphocytes from patients with active and chronic progressive MS showed the highest blastogenic stimulation in response to BP, the lowest ConA-induced suppression and the lowest absolute a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The T gamma level reportedly fluctuates with disease activity; decreasing prior to relapse and rising above normal levels during early remission [Huddlestone et al, 1979[Huddlestone et al, , 1982Traugott et al, 1982;Wicher and Holub, 1982], Several groups have reported in creased T gamma levels in chronic progres sive disease [Santoli et al, 1978;Goust et al, 1980;Merrill et al, 1980;Traugott et al, 1982], Additionally, Merrill et al [1980] found increased T gamma level during at tacks.…”
Section: Peripheral Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…The T gamma level reportedly fluctuates with disease activity; decreasing prior to relapse and rising above normal levels during early remission [Huddlestone et al, 1979[Huddlestone et al, , 1982Traugott et al, 1982;Wicher and Holub, 1982], Several groups have reported in creased T gamma levels in chronic progres sive disease [Santoli et al, 1978;Goust et al, 1980;Merrill et al, 1980;Traugott et al, 1982], Additionally, Merrill et al [1980] found increased T gamma level during at tacks.…”
Section: Peripheral Bloodmentioning
confidence: 99%
“…For example, measles-virus-in duced blastogenesis has been reported to be equal in MS and control lymphocytes [Dau and Peterson, 1970;Knowles and Saunders, 1970;Cunningham-Rundles et al, 1977;Ste wart et al, 1977;Symington and MacKay, 1978]. In other studies, the response of MS lymphocytes to measles virus was weaker than that of control lymphocytes [McFar land and McFarlin, 1979;Illonen et al, 1981;Sagar et al, 1981] and further studies have shown that MS lymphocytes responded more strongly than control lymphocytes [Walker and Cook, 1979;Walker et al, 1982], Reports involving blast transformation to neural antigens also reveal many inconsis tencies, however, the majority of reports sug gest that MS lymphocytes react to MBP [Colby et al, 1977;Gosseye-Lissoir et al, 1977;Hughes et al, 1977;Lisak and Zwei man, 1977;Lisak et al, 1981;Wicher et al, 1981;Wicher and Holub, 1982;Frick, 1982] as well as cerebrosides and gangliosides [Offner and Konat, 1980;Frick, 1982]. Al though lymphocytes from MS patients are more reactive to these neural antigens than those of healthy control individuals, the magnitude of this response is very limited (stimulation indexes < 3).…”
Section: Stimulation Assays: Search For the Elusive Ms-specific Antigenmentioning
confidence: 99%